Simvastatin is effective in killing the radioresistant breast carcinoma cells - Aschenbrenner, Bertram (Radiology and oncology (Ljubljana), 2021)
Background. Statins, small molecular 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors, are widely used to lower cholesterol levels in lipid-metabolism disorders. Recent preclinical and clinical studies have shown that statins exert beneficial effects in the management of breast cancer by increasing recurrence free survival. Unfortunately, the underlying mechanisms remain elusive. Materials and methods. Simvastatin, one of the most widely prescribed lipophilic statins was utilized to investigate potential radiosensitizing effects and an impact on cell survival and migration in radioresistant breast cancer cell lines. Results. Compared to parental cell counterparts, radioresistant MDA-MB-231-RR, T47D-RR andAu565-RR cells were characterized by upregulation of 3-hydroxy-3-methylglutharyl-coenzyme A reductase (HMGCR) expression accom-panied by epithelial-to-mesenchymal transition (EMT) activation. Radioresistant breast cancer cells can be killed by simvastatin via mobilizing of a variety of pathways involved in apoptosis and autophagy. In the presence of simvasta-tin migratory abilities and vimentin expression is diminished while E-cadherin expression is increased. Conclusions. The present study suggests that simvastatin may effectively eradicate radioresistant breast carcinoma cells and diminish their mesenchymal phenotypes.
Keywords: breast cancer; radioresistant cells; radiorezistentne celice; radioterapija; radiotherapy; rak dojke